Electrolyte for lithium ion battery and lithium ion battery applying electrolyte

By introducing components such as fluoroether compounds, hexafluorobenzene and vinylene carbonate into the lithium-ion battery electrolyte, a high heat resistance electrolyte is formed, which solves the problem of poor safety performance of lithium-ion batteries, significantly improves the battery's self-production and thermal runaway starting temperature, and reduces the risk of thermal runaway.

CN119695274AActive Publication Date: 2025-03-25EVE ENERGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411827184.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-25
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

Lithium-ion batteries containing high nickel/high silicon systems have poor safety performance and are prone to thermal runaway, which limits their large-scale industrial application.

Method used

An electrolyte solution for lithium ion batteries is provided, including fluoroether compounds, hexafluorobenzene and vinylene carbonate as the first additives, and ethylene glycol dimethyl ether as the organic solvent. Through the synergistic action of these components, a high heat resistance electrolyte solution is formed, thereby increasing the self-production starting temperature and thermal runaway starting temperature of the lithium ion battery.

Benefits of technology

Effectively inhibit the thermal runaway reaction of lithium-ion batteries, improve the safety performance of lithium-ion batteries, reduce the probability of thermal runaway occurrence, and increase the battery's self-produced thermal start temperature and thermal runaway start temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005184784010000051
    Figure BDA0005184784010000051
  • Figure BDA0005184784010000061
    Figure BDA0005184784010000061
  • Figure BDA0005184784010000062
    Figure BDA0005184784010000062
Patent Text Reader

Abstract

The invention provides an electrolyte for a lithium ion battery and the lithium ion battery applying the electrolyte. The electrolyte for the lithium ion battery comprises a first additive and an organic solvent, the mass fraction of the first additive in the electrolyte is 1.6-4.5%, and the mass fraction of the organic solvent in the electrolyte is 80-85%; the first additive comprises a fluoro-ether compound, hexafluorobenzene and vinylene carbonate, and the organic solvent comprises ethylene glycol dimethyl ether; the mass ratio of the fluoro-ether compound to the hexafluorobenzene to the vinylene carbonate is (0.1-1): (1-2): (0.5-1.5). The electrolyte provided by the invention can weaken oxygen release heat production of the high-nickel ternary positive electrode material and inhibit decomposition side reaction heat production of the electrolyte, so that generation of a thermal runaway reaction of the lithium ion battery is effectively inhibited, and the self-heat-production starting temperature and the thermal runaway starting temperature of the lithium ion battery are increased; the thermal runaway occurrence probability of the lithium ion battery containing the high-nickel ternary positive electrode material is reduced, and the safety performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrolyte for a lithium-ion battery and a lithium-ion battery using the electrolyte. Background Art

[0002] The continued prosperity of computers, communications and consumer electronics has brought about the rapid development of the lithium-ion battery industry. In particular, the rise of new energy vehicles in recent years has not only promoted the development of power lithium-ion batteries, but also put forward higher energy density and safety performance requirements for them.

[0003] The application of high-nickel ternary positive electrode materials and silicon-based negative electrode materials is an effective way to achieve high energy density in lithium-ion batteries. However, the safety performance of lithium-ion batteries containing high-nickel / high-silicon systems is poor, and they are prone to thermal runaway during actual applications, which has become one of the main bottlenecks restricting their large-scale industrial applications. By lowering the self-heating starting temperature and thermal runaway starting temperature of lithium-ion batteries, the time for lithium-ion batteries to trigger thermal runaway can be effectively delayed and the probability of thermal runaway of lithium-ion batteries can be effectively reduced or the occurrence of thermal runaway of lithium-ion batteries can be prevented. Therefore, it is extremely important to develop an electrolyte that can increase the self-heating starting temperature and thermal runaway starting temperature of lithium-ion batteries to improve the safety performance of lithium-ion batteries containing high-nickel / high-silicon systems. Summary of the invention

[0004] In order to solve the problem of poor safety performance of existing lithium-ion batteries containing high nickel / high silicon systems, increase the self-heating starting temperature and thermal runaway starting temperature of lithium-ion batteries, and reduce the risk of thermal runaway of lithium-ion batteries, the present application provides an electrolyte for lithium-ion batteries and a lithium-ion battery using the same.

[0005] According to the first aspect of the present application, there is provided an electrolyte for a lithium ion battery, the electrolyte comprising a first additive and an organic solvent, the mass fraction of the first additive in the electrolyte being 1.6-4.5%, and the mass fraction of the organic solvent in the electrolyte being 80-85%; the first additive comprising a fluoroether compound, hexafluorobenzene and vinylene carbonate, the organic solvent comprising ethylene glycol dimethyl ether; calculated by mass ratio, the fluoroether compound: hexafluorobenzene: vinylene carbonate = 0.1-1: 1-2: 0.5-1.5, for example, the first additive is The mass fraction in the electrolyte can be 1.6%, 2.0%, 2.5%, 3.5%, 4.0%, 4.5%, the mass fraction of the organic solvent in the electrolyte can be 80%, 81%, 82%, 83%, 84%, 85%, the mass ratio of fluoroether compounds, hexafluorobenzene, and vinylene carbonate can be 0.1:1:0.5, 0.5:1.5:1, 1:2:1.5, 0.1:2:1.5, 1:1:0.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0006] The electrolyte for lithium-ion batteries provided by the present application introduces fluoroether compounds, hexafluorobenzene and vinyl carbonate as the first additive, and uses ethylene glycol dimethyl ether as the organic solvent. The fluoroether compound (TTE) contains a strongly polar CH group, and hexafluorobenzene has good thermal stability. TTE, hexafluorobenzene and vinyl carbonate (VC) are introduced into ethylene glycol dimethyl ether (DME). First, the coordination of DME, TTE and hexafluorobenzene can form an intermolecular anchoring effect through hydrogen bonds, and at the same time, the electrolyte has high heat resistance, thereby effectively reducing the electron cloud density on the oxygen atom, greatly improving the antioxidant capacity of the organic solvent, and then weakening the oxygen release heat generation and inhibition of electrolysis of the high-nickel ternary positive electrode material. The decomposition side reaction of the liquid generates heat, which effectively inhibits the thermal runaway reaction of the lithium-ion battery, increases the starting temperature of the self-heating and the starting temperature of the thermal runaway of the lithium-ion battery, greatly reduces the probability of thermal runaway of the lithium-ion battery containing high-nickel ternary positive electrode materials, and greatly improves the safety performance of the lithium-ion battery. Secondly, the introduction of vinylene carbonate (VC) can promote the electrochemical reaction on the surface of the negative electrode during the initial charge and discharge of the lithium-ion battery to form a solid electrolyte interface film (SEI film), effectively inhibits the embedding of organic solvent molecules and the gas expansion phenomenon of the lithium-ion battery, and can improve the safety performance of the lithium-ion battery to a certain extent, and reduce the risk of thermal runaway of lithium-ion batteries containing silicon-based materials.

[0007] Preferably, the fluorinated ether compound includes at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2,2-trifluoroethyl ether, and hexafluoroisopropyl methyl ether.

[0008] Preferably, the electrolyte further comprises a second additive, and the mass fraction of the second additive in the electrolyte is 0.1-1%. For example, the mass fraction of the second additive in the electrolyte may be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the second additive comprises at least one of lithium difluorooxalatoborate (LiDFOB) and lithium bis(oxalatoborate) (LiBOB).

[0009] This solution introduces a second additive LiDFOB and / or LiBOB into the electrolyte and applies the electrolyte to a lithium-ion battery, which is beneficial to reducing the impedance of the lithium-ion battery and improving the high-temperature cycle life of the lithium-ion battery.

[0010] Preferably, the electrolyte further includes a lithium salt, and the mass fraction of the lithium salt in the electrolyte is 10-20%; the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0011] Preferably, the lithium salt is mixed with lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI) in a mass ratio of 9 to 15:1 to 5. For example, the mass ratio of LiPF6 and LiFSI can be 9:1, 12:3, 15:5, 9:5, 15:1, 12:1, 12:3, 12:5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] In this scheme, LiPF6 and LiFSI are compounded according to the above-mentioned mass ratio as the lithium salt in the electrolyte. It has good thermal stability and is insensitive to moisture. It can reduce the side reactions between the electrolyte and the positive and negative electrodes and increase the decomposition temperature of the electrolyte, which is beneficial to improving the safety of the electrolyte. At the same time, it improves the high-temperature cycle performance of the lithium-ion battery using the electrolyte, reduces the risk of thermal runaway of the lithium-ion battery in actual application, and improves the safety performance of the lithium-ion battery.

[0013] Preferably, the above-mentioned organic solvent also includes cyclic carbonate solvents and linear carbonate solvents; the cyclic carbonate solvents include at least one of ethylene carbonate (EC), propylene carbonate (PC), and fluoroethylene carbonate (FEC); the linear carbonate solvents include at least one of ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC).

[0014] Preferably, the above-mentioned organic solvent includes propylene carbonate, fluoroethylene carbonate and dimethyl carbonate. Calculated by mass ratio, ethylene glycol dimethyl ether: propylene carbonate: fluoroethylene carbonate: dimethyl carbonate = 20-30: 10-22.5: 5-15: 25-36. For example, the mass ratio of ethylene glycol dimethyl ether, propylene carbonate, fluoroethylene carbonate and dimethyl carbonate can be 20: 10: 5: 25, 25: 16: 10: 31, 30: 22.5: 15: 36, 20: 17: 10: 25, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Ethylene carbonate (EC) will intensify the oxygen release reaction and heat generation of the ternary high-nickel positive electrode, thereby causing thermal runaway of the lithium-ion battery. Compared with ethylene carbonate (EC), propylene carbonate (PC) has higher thermal stability, and has the effect of increasing the starting temperature of self-heat generation and the starting temperature of thermal runaway, and weakening the oxygen release and heat generation of the positive electrode.

[0016] In this scheme, propylene carbonate (PC), fluoroethylene carbonate (FEC) and dimethyl carbonate (DMC) are compounded according to the above mass ratio as the organic solvent in the electrolyte. The hexafluorobenzene in the electrolyte has a synergistic effect with PC, FEC and DMC to reduce the impedance of the lithium-ion battery using the electrolyte, which is beneficial to improving the cycle stability of the lithium-ion battery.

[0017] According to a second aspect of the present application, a lithium ion battery is provided, the lithium ion battery comprising the above-mentioned electrolyte for lithium ion batteries.

[0018] Preferably, the lithium-ion battery further comprises a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active coating disposed on at least one surface of the positive electrode current collector, the positive electrode active coating comprising a ternary positive electrode material LiNi x Co y M 1-x-y O2, wherein 0.6≤x<1, 0<y<0.4, M is selected from one of Mn and Al, for example, x can be 0.6, 0.7, 0.8, 0.9, y can be 0.1, 0.2, 0.3, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0019] Preferably, the lithium-ion battery further comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating disposed on at least one surface of the negative electrode current collector, and the negative electrode active coating contains a silicon-carbon material.

[0020] Preferably, the silicon content in the silicon-carbon material is 5 to 30 wt%. For example, the silicon content in the silicon-carbon material can be 5%, 10%, 15%, 20%, 25%, or 30%. However, the silicon content is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] The electrolyte provided by the present application is applied to lithium-ion batteries containing a high-nickel / high-silicon system, which can effectively inhibit the generation of thermal runaway reactions in lithium-ion batteries, thereby increasing the self-heating starting temperature and thermal runaway starting temperature of the lithium-ion batteries, greatly reducing the probability of thermal runaway in lithium-ion batteries containing high-nickel ternary positive electrode materials and high-silicon negative electrode materials, and greatly improving the safety performance of lithium-ion batteries. DETAILED DESCRIPTION

[0022] The following is a further clear and complete description of the technical features in the technical solution provided by this application in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of this application.

[0023] Examples 1 to 3 and Comparative Examples 1 to 4

[0024] Examples 1 to 3 and Comparative Examples 1 to 4 provide a lithium ion battery, which is prepared by the following steps:

[0025] 1. Preparation of positive electrode

[0026] The ternary cathode material LiNi 0.8 Co 0.1 Mn 0.1 O2, binder polyvinylidene fluoride (PVDF) and conductive agent acetylene black were mixed in a mass ratio of 98.5:1.3:0.2 and added into solvent N-methylpyrrolidone (NMP), mixed evenly, and a positive electrode slurry with a solid content of 45% was prepared. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil (thickness of 12 μm) to form a positive electrode active coating. After vacuum drying, a compaction density of 1.4 g / cm 3 The positive electrode.

[0027] 2. Preparation of negative electrode

[0028] Silicon-carbon material (silicon content is 20wt%), binder sodium carboxymethyl cellulose (CMC) and conductive agent conductive carbon black (SP) are mixed in a mass ratio of 96:3:1 and added to a solvent deionized water, mixed evenly, to obtain a negative electrode slurry with a solid content of 45%. The negative electrode slurry is coated on both surfaces of a negative electrode current collector copper foil (thickness is 6μm) to form a negative electrode active coating. After vacuum drying, a negative electrode sheet is obtained.

[0029] 3. Preparation of Diaphragm

[0030] A polyethylene (PE) film containing a ceramic layer was used as the separator (the total thickness of the separator was 12 μm).

[0031] 4. Preparation of Electrolyte

[0032] The specific components of the electrolyte are shown in Table 1. The electrolyte is prepared by the following steps: dissolving a lithium salt in an organic solvent to prepare a lithium salt solution, adding a first additive and a second additive to the lithium salt solution, and mixing them uniformly to prepare an electrolyte, wherein TTE is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and THF is tetrahydrofuran.

[0033] Table 1 Specific components of the electrolyte of the lithium ion battery of Examples 1 to 3 and Comparative Examples 1 to 4

[0034]

[0035] 5. Assembly and formation of lithium-ion batteries

[0036] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell, which is placed in an outer packaging shell, dried and injected with the above-mentioned electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.

[0037] Comparative Examples 5 to 10

[0038] Comparative Examples 5 to 10 provide a lithium ion battery. Compared with Example 1, the difference in structure is that the components of the electrolyte are different, as shown in Table 2.

[0039] Table 2 Specific components of the electrolyte of the lithium ion battery of Example 1 and Comparative Examples 5 to 10

[0040]

[0041] Except for the above differences, the materials, formulation ratios and preparation operations used in Comparative Examples 5 to 10 are strictly consistent with those in Example 1.

[0042] Embodiments 4 to 10

[0043] Embodiments 4 to 10 provide a lithium-ion battery. Compared with Embodiment 1, the difference in structure is that the components of the electrolyte are different, as shown in Table 3.

[0044] Table 3 Specific components of the electrolyte of the lithium ion battery of Example 1 and Examples 4 to 10

[0045]

[0046]

[0047] Except for the above differences, the materials, formulation ratios and preparation operations used in Examples 4 to 10 are strictly consistent with those in Example 1.

[0048] Comparative Example 11 and Example 11

[0049] Example 11 and Comparative Example 11 provide a lithium ion battery. Compared with Example 1, the difference in structure is that the components of the electrolyte are different, as shown in Table 4.

[0050] Table 4 Specific components of the electrolyte of the lithium ion battery of Example 1, Comparative Example 11 and Example 11

[0051]

[0052]

[0053] Except for the above differences, the materials, formula ratios and preparation operations used in Comparative Example 11 and Example 11 are strictly consistent with those in Example 1.

[0054] Test Case

[0055] 1. Participants

[0056] In this test example, the lithium ion batteries prepared in Examples 1 to 11 and Comparative Examples 1 to 11 were used as test objects to conduct relevant performance tests.

[0057] 2. Test content

[0058] (1) 150℃&0.5h-No-fixture thermal abuse thermal runaway time and temperature monitoring test

[0059] After the lithium-ion battery is fully charged (state of charge 100% SOC), it is placed in a temperature box and heated from room temperature to 150±2°C at a rate of 5°C / min. The temperature is maintained for 30 minutes and then the heating is stopped. The battery is observed for 1 hour. Two parallel experiments are performed for each embodiment or comparative example to observe whether the lithium-ion battery catches fire. At the same time, the temperature changes of the lithium-ion battery (thermal runaway T2 delay time, thermal runaway triggering T2 temperature, thermal runaway peak temperature T3) are recorded. The thermal runaway T2 delay time of comparative example 1 refers to the temperature during the heating process. The heating time when the thermal runaway starting temperature is reached, and the thermal runaway T2 delay time of Examples 1 to 11 and Comparative Examples 2 to 11 is relative to Comparative Example 1, that is, it is calculated by subtracting the heating time when the lithium ion batteries of Examples 1 to 11 and Comparative Examples 2 to 11 reach the thermal runaway starting temperature during the heating process from the heating time when the lithium ion battery of Comparative Example 1 reaches the thermal runaway starting temperature during the heating process; thermal runaway triggering temperature T2 - temperature rise rate greater than 1°C / min; thermal runaway peak temperature T3 - thermal runaway maximum temperature.

[0060] (2) Accelerating Rate Calorimeter (ARC) Thermal Runaway Test

[0061] The working principle of the Accelerating Rate Calorimeter (ARC) is to provide a (nearly) adiabatic environment and perform step heating on the lithium-ion battery through the "Heat-Wait-Seek" mode to simulate the thermal runaway process of the lithium-ion battery when there is no heat exchange between the lithium-ion battery and the environment.

[0062] After the lithium-ion battery is fully charged (state of charge 100% SOC), it is placed in the ARC calorimetric chamber (nitrogen atmosphere) to measure the temperature changes of the ion battery (self-heating starting temperature T1, thermal runaway starting temperature T2, maximum temperature T max) are recorded. The three characteristic temperatures of thermal runaway of lithium batteries are as follows: self-heating starting temperature T1 - temperature rise rate greater than 0.01℃ / min; thermal runaway trigger / starting temperature T2 - temperature rise rate greater than 1℃ / min; thermal runaway maximum temperature T max .

[0063] 3. Experimental results

[0064] Table 5 Thermal runaway time and temperature monitoring test results of lithium-ion batteries at 150℃ and 0.5h without fixture thermal abuse

[0065]

[0066]

[0067] Table 6 Lithium-ion battery ARC thermal runaway test results

[0068]

[0069]

[0070] The thermal runaway time and temperature monitoring test results of the lithium-ion batteries provided by Examples 1 to 11 and Comparative Examples 1 to 11 under 150°C & 0.5h without fixture thermal abuse are shown in Table 5, and the ARC thermal runaway test results of the lithium-ion batteries provided by Examples 1 to 11 and Comparative Examples 1 to 11 are shown in Table 6, wherein, in Table 5, the latter 2PCS in "2PCS / 2PCS fire" refers to the total number of lithium-ion batteries being 2, and the former 2PCS refers to the number of lithium-ion batteries that caught fire being 2.

[0071] From the temperature rise curve of the battery during the 150°C hot box test, it can be seen that the thermal runaway time of the lithium-ion batteries provided by Examples 1 to 3 is about 13 to 22 minutes longer than that of the lithium-ion battery provided by Comparative Example 1, and the thermal runaway triggering temperature T2 is increased by about 10 to 45°C, which greatly reduces the T3 temperature by about 300°C. From the battery ARC thermal runaway T1 / T2 / T max The temperature test shows that the thermal runaway time of the lithium-ion batteries provided in Examples 1 to 3 is 19 to 20°C higher than that of the lithium-ion battery provided in Comparative Example 1, and the self-generated heat T1 temperature is 19 to 20°C higher and the thermal runaway triggering T2 temperature is 20 to 24°C higher. The above results indicate that the thermal runaway of the lithium-ion batteries provided in Examples 1 to 3 is delayed and the probability of thermal runaway is reduced, thereby improving the safety of the lithium-ion batteries.

[0072] Compared with Example 1, the electrolyte in the lithium ion battery provided in Comparative Example 2 does not contain VC, the electrolyte in the lithium ion battery provided in Comparative Example 3 does not contain hexafluorobenzene, the electrolyte in the lithium ion battery provided in Comparative Example 4 does not contain DME, the mass fraction of the first additive contained in the electrolyte of the lithium ion batteries provided in Comparative Examples 5 and 6 does not meet 1.5-3.5%, the mass fraction of the first additive contained in the electrolyte of the lithium ion batteries provided in Comparative Examples 7 and 8 meets 1.5-3.5%, but the mass ratio of hexafluorobenzene to vinylene carbonate does not meet 1-2:0.5-1.5. The test results show that the lithium batteries provided in Comparative Examples 2 to 8 are less than Example 1 in the 150°C hot box test in thermal runaway T2 delay time and thermal runaway triggering T2 temperature, and the thermal runaway peak temperature T3 are higher than Example 1. In the ARC thermal runaway test, the self-heating starting temperature T1 and the thermal runaway starting temperature T2 are lower than Example 1, and the maximum temperature T max All are higher than Example 1.

[0073] Compared with Example 1, the content of the second additive contained in the electrolyte of the lithium ion batteries provided in Examples 4 and 5 does not meet 0.1-1%, and the lithium salt contained in the electrolyte of the lithium ion batteries provided in Examples 7 and 8 does not meet 10-20%. The test results show that the thermal runaway T2 delay time and the thermal runaway triggering T2 temperature of the lithium batteries provided in Comparative Examples 2 to 8 are both less than that of Example 1 in the 150°C hot box test, and the thermal runaway peak temperature T3 is higher than that of Example 1. In the ARC thermal runaway test, the self-heating starting temperature T1 and the thermal runaway starting temperature T2 are both lower than those of Example 1, and the maximum temperature T max All are higher than Example 1.

[0074] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.

Claims

1. An electrolyte for a lithium ion battery, characterized in that: The electrolyte comprises a first additive and an organic solvent, wherein the mass fraction of the first additive in the electrolyte is 1.6-4.5%, and the mass fraction of the organic solvent in the electrolyte is 80-85%; The first additive includes a fluorinated ether compound, hexafluorobenzene and vinylene carbonate, and the organic solvent includes ethylene glycol dimethyl ether; Calculated by mass ratio, the fluoroether compound: the hexafluorobenzene: the vinylene carbonate = 0.1-1: 1-2: 0.5-1.

5.

2. The electrolyte for lithium ion battery according to claim 1, characterized in that: The fluorinated ether compound includes at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2,2-trifluoroethyl ether, and hexafluoroisopropyl methyl ether.

3. The electrolyte for lithium ion battery according to claim 1, characterized in that: The electrolyte further comprises a second additive, wherein the mass fraction of the second additive in the electrolyte is 0.1 to 1%; The second additive includes at least one of lithium difluorooxalatoborate and lithium bisoxalatoborate.

4. The electrolyte for lithium ion battery according to claim 1, characterized in that: The electrolyte further comprises a lithium salt, wherein the mass fraction of the lithium salt in the electrolyte is 10 to 20%; The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide.

5. The electrolyte for lithium ion battery according to claim 4, characterized in that: The lithium salt is prepared by mixing the lithium hexafluorophosphate and the lithium bis(fluorosulfonyl)imide in a mass ratio of 9-15:1-5.

6. The electrolyte for lithium ion battery according to claim 1, characterized in that: The organic solvent also includes cyclic carbonate solvents and linear carbonate solvents; The cyclic carbonate solvent includes at least one of ethylene carbonate, propylene carbonate and fluoroethylene carbonate; The linear carbonate solvent includes at least one of ethyl methyl carbonate and dimethyl carbonate.

7. The electrolyte for lithium ion battery according to claim 6, characterized in that: The organic solvent comprises propylene carbonate, fluoroethylene carbonate and dimethyl carbonate, and the mass ratio is ethylene glycol dimethyl ether: the propylene carbonate: the fluoroethylene carbonate: the dimethyl carbonate=20-30:10-22.5:5-15:25-36.

8. A lithium ion battery, characterized in that: The lithium ion battery comprises the electrolyte for a lithium ion battery according to any one of claims 1 to 7.

9. The lithium-ion battery according to claim 8, characterized in that: The lithium-ion battery further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active coating comprises a ternary positive electrode material LiNi x Co y M 1-x-y O2, wherein 0.6≤x<1, 0<y<0.4, and the M is selected from one of Mn and Al.

10. The lithium ion battery according to claim 8, characterized in that: The lithium-ion battery further comprises a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active coating contains a silicon-carbon material.

11. The lithium ion battery according to claim 10, characterized in that: The silicon content in the silicon-carbon material is 5-30wt%.

Citation Information

Patent Citations

  • Anode-free lithium battery

    CN115443570A

  • Electrochemical device and electronic device

    CN116404262A

  • Electrolyte formulations

    US20150214577A1

  • Nonaqueous electrolytic solution and lithium ion secondary battery

    US20190181494A1

  • Lithium ion battery

    US20230402653A1